Application of suspended ion exchange, in-line coagulation and ceramic membranes for surface water treatment - Metcalfe, David Christopher (Cranfield University, 2016)
A long term, large scale pilot study was performed to assess the use of a novel process based on suspended ion exchange (SIX®) and in-line coagulation (ILCA®) pretreatment for ceramic membrane filtration (CeraMac®), for treating three variable quality UK surface waters. SIX was shown to remove similar quantities of dissolved organic carbon (DOC) to coagulation for low to moderate DOC source waters. However, during periods of high DOC concentrations and high specific UV absorbance, the removal of organic compounds was reduced. The long term DOC removal data for the SIX process indicated good performance, which was in line with previously reported results from studies using other suspended ion exchange processes. Organic characterisation using liquid chromatography–organic carbon detection (LC-OCD) revealed the differing selectivities of the SIX and ILCA processes, for low and high molecular weight organic fractions respectively. When these processes were used in combination, a broad range of organic compounds were removed, leading to a 50% reduction in DOC concentration in comparison with an existing full scale conventional treatment process. Subsequently, disinfection by-product (DBP) formation was significantly reduced (62% vs. the conventional process) due to the lower DOC concentration, reduced specific reactivity of the residual organic compounds and reduced formation of brominated DBPs. Removal of high molecular weight organic compounds (biopolymers) was shown to be critical for stable operation of ceramic membranes at high flux. Optimised in-line coagulation (ILCA) pretreatment (which flocculated the biopolymers) led to negligible membrane adsorption of organic compounds, as low molecular weight (LMW) fractions (which are recalcitrant to coagulation) were shown not to be retained by the membrane. Due to this, when using optimised ILCA, additional removal of LMW organic fractions by using SIX in combination with ILCA provided no measureable benefit with regards to membrane fouling suppression. Automation of coagulant dosing was achieved for the high SUVA waters tested, using simple feed forward control based on the UV transmittance of the feed water. The application of this automated system led to very low membrane fouling rates (0.24kPa/day), despite highly challenging operating conditions of elevated fluxes (185 L m- 2 h- 1 ) and highly variable feed water dissolved organic carbon concentrations (1-10mg/l).
Keywords: Disinfection by-products; Natural organic matter; Ceramic membrane fouling; Pretreatment; Suspended ion exchange; In-line coagulation; Liquid chromatography-organic carbon detection